Chronic histamine 3 receptor antagonism alleviates depression like conditions in mice via modulation of brain-derived neurotrophic factor and hypothalamus-pituitary adrenal axis. (March 2019) - Kumar, Ajeet; Dogra, Shalini; Sona, Chandan; Umrao, Deepmala; Rashid, Mamunur; Singh, Sandeep K; Wahajuddin, Muhammad; Yadav, Prem N
Highlights: Chronic H3R antagonism alleviates CUS induced depression-like phenotypes. Chronic treatment of H3R antagonist increases BDNF expression in PFC and hippocampus of CUS treated mice. Histamine treatment increases BDNF expression in primary cortical neurons via H4R. Chronic H3R antagonist resets the overactive HPA axis due to chronic stress. Abstract: The last two decades of research has established histamine (HA) as a neurotransmitter. Since H3R antagonists are known to modulate several neurotransmitters besides HA, H3R antagonists have shown potential for the treatment of different central nervous system disorders, including depression. However, molecular mechanisms underlying the beneficial effects of H3R antagonism in depression are not clear, yet. In the present study, we investigated the antidepressant potential of ciproxifan, a selective H3R antagonist, in chronic unpredictable stress (CUS) model of depression in C57BL/6 J mice. We observed that chronic treatment of CUS mice with ciproxifan (3 mg/kg i.p .; for three weeks) alleviates depression-like symptoms such as helplessness measured by forced swim and tail suspension test (FST and TST), anhedonia measured by sucrose preference test (SPT) and social deficit measured in social behavior test. Chronic ciproxifan treatment restored CUS induced BDNF expression in the prefrontal cortex (PFC) and hippocampus. We also observed that ciproxifan modulates CUS induced NUCB2/nesfatin-1 and CRH expression in the hypothalamus and plasma corticosterone. We also determined the direct effect of HA on BDNF expression in neurons by western blotting and immunocytochemistry, and found that HA significantly induced BDNF expression, which was blocked by the H4R selective antagonist, but not by other HA receptor selective antagonists. Furthermore, ciproxifan significantly modulated NMDA glutamate receptor subunits NR2B and NR2A. Thus, these results suggest that increased HA signaling in the brain produces antidepressant-like effects in mice and modulates BDNF expression and HPA-axis.